(untitled) (Scientific journal of the Fergana State University, 2025)
The article tells that in the development of Uzbekistan, the expression “New Uzbekistan” remains a tool that contributes to the development of society. This creates the need to study and develop the prospects of a national ideological strategy in ensuring the sustainability of society. Accordingly, the national idea is equally important for all countries and societies of the world. Each nation, at crucial moments in its history, solves first of all the issue of ideology, the problem of forming a social idea, which forms its core, acts as a kind of unifying core. The national idea of the development of our country today’s practical significance of the issue lies in the fact that we have gone through a transitional new stage of development. It was at this time that conditions were created for the formation of views that protect the interests of various segments of the population. This article reveals the socio-philosophical significance of the realization of the national idea that today, in the stability of society, the spiritual and moral aspects of “human interests above all”, “the richer the people, the richer and more powerful the state”, “the people should not serve state bodies, but state bodies should serve the people”.